PENGARUH TIME BUDGET PRESSURE TERHADAP PERILAKU DISFUNGSIONAL DAN KUALITAS AUDIT PADA AUDITOR BPK JAWA TENGAH TAHUN 2008 - Warno, Warno (JURNAL STIE SEMARANG, 2010)
The  purpose   of  this   study   is  to  investigate    the   time   budget   pressure  for disfungtional    auditor's   behavior   at financial   audit  agency  in  Central  Java.  The primary   issue discussed  in this  study  is quality   audit.   The effect  of  time  budget pressure    to  audit's    quality    is  directly    and   through    the   intermediaries     of disfungtional    behavior  (under  reporting   of time, premature   sign off and replacing of  audit  procedure).   To examine   these  issues, Interview,   documentation    and  a mailing   survey  were  distributed   to auditors  of Financial  Audit  Agency  in Central Java.  The Structural   Equation  Modeling   (SEM) is used for  developing   theoretical and  analyzing   data.   The result  indicates   that  time  budget  pressure  as a main exogenous    variable    influence    audit's     quality     both    directly     and    through intermediaries,   disfungtional    behavior  (premature   sign off  and replacing  of audit procedure).   This findings   reflect  that  allocation  oftime   budget  is important   issue. The study  result  time'  budget.  pressure  can  effect  to auditor   to have  behavior disfungtional    (premature   sign off and replacing  of audit  procedure)  and the effect of  this  behaviour   does  not  reduce  audit  quality,   this  result  supported   by from interview   and they  recognized  that  there  is a disflJngtional   behaviour  of auditor, however,  this is on the prefessi"onal attitude   and if there  is a less dudit  time, some certain  rules  might  be lenghten   the  time,  so how  quality  of audit  in BPK (Badan Pemeriksa  Keuangan)   is not caused by the time.